Multi-Factor Authentication Using a Smart Card and Fingerprint (Case Study: Parking Gate) - Isa Mulia Insan; Parman Sukarno; Rahmat Yasirandi (School of Computing, Telkom University, 2019)
Security is one of the considerations in the development of smart parking. In Indonesia, the most common authentication factor is using a smart card as an authentication factor at the gate. Using a smart card as an authentication factor has loopholes that can be misused. Accordingly, authentication system needs an additional factor (more than one). Authentication that uses more than one factor is also called Multi-Factor Authentication (MFA). However, the MFA applied to smart parking can still be misused. The cause of the MFA can be misused because the MFA cannot ensure the user's smart card. Therefore, we apply the MFA at the gate in smart parking using a two-factor authentication system on this research. These two factors are the smart card and biometric data (fingerprint). This authentication system can prove the hypothesis that if the smart card lost, the smart card cannot be used by other than the owner (H0) and the smart card whose data has been rewritten or cloned cannot be a threat to the system (H1). Proofing of this hypothesis is bypassing several attack scenarios. Thus, the security of the proposed parking gate system can be guaranteed.